PH/enzyme dual sensitive and nucleus-targeting dendrimer nanoparticles to enhance the antitumour activity of doxorubicin. (16th March 2022) - Wu, Zi-Yan; Shen, Jian-Min; Lang, Hao; Yue, Ting; Sun, Chan
Abstract: Direct delivery of drugs into the nucleus is a promising nanotechnology therapy, since the nucleus is one of the most important organelles controlling cell proliferation and apoptosis. Here, we report a nucleus-targeting nanocarrier for nuclear drug delivery using a pH/enzyme dual sensitive strategy. The specific ligand PGM (PKKKRKV-GFLG-Mp), composed of nuclear localization sequence (PKKKRKV), enzyme-sensitive tetrapeptide (Gly-Phe-Leu-Gly, GFLG), and pH-sensitive molecules morpholine (Mp), was modified on poly (amidoamine) (PAMAM) by maleimide active polyethylene glycol ester (NHS-PEG-MAL) to form PAMAM-PEG-PGM. Doxorubicin (DOX) was loaded into the cavity of PAMAM to prepare DOX/PAMAM-PEG-PGM. In vitro release study suggested DOX release from DOX/PAMAM-PEG-PGM nanoparticles followed pH and enzyme-triggered manner. In vitro studies showed DOX/PAMAM-PEG-PGM nanoparticles could not only promote cell internalization through the charge switching of morpholine, but also achieve nuclear internalization by the mediation of composite formed by NLS and importin α/β receptor. Further, employing H22 tumour-bearing BALB/c mice as a model, the systemic distribution and anticancer effects of nanoparticles were studied in vivo . The results indicated the nanoparticles could preferentially accumulate in the tumour site in vivo, and the tumour inhibition rate was 88.47%. In short, the nanoparticles developed could be promising in application to nucleus-targeting therapy to enhance antitumour activity.